Optoelectronic and thermoelectric characteristics of halide based double perovskites K2YAgX6 (X = Br, I) for energy storage applications. (1st January 2023) - Mustafa, Ghulam M.; Slam, Abdul; Saba, Sadaf; Noor, N.A.; Waqas Iqbal, M.; Dahshan, A.
Graphical abstract: Highlights: Halide based double perovskites K2 YAgX6 (X = Br, I) have been theoretically investigated using WEIN2k software. Structural parameters were optimized using the Perdew–Burke–Ernzerhof generized gradient approximation (PBEsol-GGA) Investgation of the mechanical response of these materials revealed their ductile nature. An indirect band gap nature with bang gap values of 3.4 and 2.6 eV were estimated using mBJ potential. Electronic transport properties over a wide range of temperatures have been evaluated. Abstract: The halide based double perovskites K2 YAgBr6 and K2 YAgI6 have been extensively investigated for their optoelectronic properties using the full-potential linearized augmented plane wave method. Their thermodynamic and structural stabilities were mapped by computing the enthalpy of formation and tolerance factor respectively, which revealed that K2 YAgBr6 is more stable. The computed values of the structural parameters in the ground state showed that the unit cell expands upon replacement of Br with I, which is explained based on their relative ionic radii. The Poisson and Pugh ratio were calculated, based on the elastic constants, which argued the ductile nature of these double perovskites. The presence of band edges at two different symmetry points proclaimed their indirect bandgap nature and the bandgap value decreases upon replacement of Br with I. The computation of optical parameters manifested an increasing trend in the dielectric constant, refractive index and reflectivity when Br is substituted with I. Semi-classical Boltzmann theory-based BoltzTraP code is employed to estimate different thermoelectric parameters, including the power factor and figure of merit, which exhibited the potential of these materials for optoelectronic and thermoelectric devices.